PENINGKATAN KEMAMPUAN MEMBACA EKSTENSIF DENGAN MENERAPKAN METODE SQ3R SISWA KELAS VIII F SMPN 1 KASIMBAR - Suparni Suparni (BAHASANTODEA, 2016)
The problems examined in this study 1) how the application of methods to improve reading ability SQ3R extensive class VIII SMPN 1 Kasimbar F, 2) how the increased ability to read extensively by applying the method SQ3R F class VIII SMPN 1 Kasimbar. There is also the purpose of this study 1) aims to describe the application of methods to improve reading ability SQ3R extensive class VIII SMPN 1 Kasimbar F, 2) aims to describe the results of an extensive improvement of reading skills by applying the method SQ3R F class VIII SMPN 1 Kasimbar, this study performed two cycles, ie cycle I and cycle II with a target value of the average grade of at least 75 individual kentutasan and classical minimal 80. This research uses a follow-class research. This research uses design research model Kemmis and MC. Tagart, this research is done through the process of planning, action, observation, and reflection. Data collection cycle I and II using the test techniques and nontes. Based on the results of the assessment cycle I and cycle II is to determine the contents of paragraph earn 87 rose to 116, determines the content of the news equation 71 rose to 109, determines the difference of news content 85 rose to 111, specify the appropriate information ADIKSIMBA news ketercapain 76 students rose to 114, and concluded 76 news content rose to 105 with the average value of 61.71% first cycle classes. Students who otherwise completed as many as 4 people or 12.5% and students who otherwise did not complete as many as 28 people or 87.5% of the vote the first cycle the average value obtained grade students only reached 64.84% with a classical mastery 18.75 %. Sisklus I read the test results extensively through SQ3R methods have not been successful otherwise. Learning outcomes extensive reading cycle II has demonstrated success with an average grade of 86.25% or completeness mecapai classically by 90.62%. From these findings it can be seen that there is a significant increase from the first cycle to the second cycle so that it can be concluded learning to read extensively by applying SQ3R methods can be improved. It is evident from the first cycle to the second cycle of completeness students increased to 72.37%, so that the target value of KKM can be realized. Keywords: reading extensive, the method SQ3R